PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI FINANSIAL, DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA KARYAWAN PADA PT. BPR NUSANTARA BONA PASOGIT 7 PEMATANG RAYA - Purba, Gresia Ruth Elsani; Sinaga, Ria Veronica (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine and explain the influence of leadership style, financial compensation and non-financial compensation on employee performance at PT. BPR Nusantara Bona Pasogit 7 Pematang Raya. Data collection was carried out through questionnaires and documentation techniques. The research method used is quantitative, with 35 respondents taken using saturated or census sampling. Data analysis in this study used SPSS version 25. The test results prove that partially leadership style, financial compensation has a positive and significant effect on employee performance, and non-financial compensation has a positive effect on employee performance, and simultaneously leadership style, financial compensation and non-financial compensation has a significant effect on employee performance. The coefficient of determination (R Square) is 0.868, meaning that employee performance can be explained by the variable leadership style, financial compensation and non-financial compensation of 86.8%, while another 13.2% is explained by other variables not explained in this study, such as work discipline, communication and enthusiasm.